Periclimenaeus dactylodon sp. nov. (Decapoda: Pontoniinae), from Heron Island, Queensland, Australia - Bruce, A. J. (Zootaxa, 2012)
A new species of Periclimenaeus (Crustacea: Pontoniinae) from Heron Island, Queensland, Australia, is described andillustrated. Periclimenaeus dactylodon sp. nov., an ascidian associate, was collected from a coral reef at 25 m and increases to 17 the number of Periclimenaeus known from Heron Island and to 23 the number of species known from Australia.